Trap-assisted precision spectroscopy of forbidden transitions in highly-charged ions - Vogel, Manuel; Quint, Wolfgang (Physics reports, 2010)
Spectroscopic properties of highly charged ions contain valuable information both about atomic and nuclear properties of these systems and open new ways to access fundamental quantities. Experimental approaches to precision spectroscopy especially of forbidden transitions are manifold with novel Penning-trap assisted methods under implementation which build a bridge between optical and microwave spectroscopy. In doing so, they allow experimental links between transition frequencies and both electronic and nuclear magnetic moments of these ions. The absence of diamagnetic shielding in few-electron ions makes a direct measurement of nuclear magnetic moments possible. With the use of novel confinement and manipulation techniques, the experimental precision can be significantly increased and the necessity for optical detection of fluorescence photons can be circumvented, thus allowing the exploration of frequency regions where detectors are unavailable. We discuss spectroscopic techniques applied to highly charged ions with relative accuracies ranging from about 10−3 to beyond 10−10, thus even allowing one to ‘weigh’ electronic excitation energies by their relativistic mass equivalent.
Online veröffentlicht am 11. Dezember 2009
Gesehen am 12.09.2023